MiMO - Oon, Shannon Qian Yi (2014)
MiMO is a joint Final Year Project between two students; Oon Qian Yi Shannon and Chang Pei Yee, majoring in Digital Animation. MiMO is inspired by Joan Miró paintings’ lines and colours.